IMPLEMENTASI KEBIJAKAN SERTIFIKASI GURU DALAM JABATAN DI DINAS PENDIDIKAN KABUPATEN CIREBON - Samsul Arifin; Heriyani Agustina; Nursahidin Nursahidin (Jurnal Ilmiah Publika, 2015)
ABSTRACT This research is a qualitative research using verbal data from respondents' information about the implementation of the teacher certification policy in a position at the Cirebon District Education Office. Data collection techniques use interviews, observation, and documentation. The selection of informants used purposive sampling technique. Data analysis in this study uses qualitative descriptive analysis with data reduction and data display stages.The implementation study is a study of policy studies that lead to the implementation process of a policy. In practice policy implementation is a process that is so complex that it is not infrequently politically charged with the intervention of various interests. This study uses the theory of George C. Edward III. In this theory, the success of a policy implementation is influenced by four factors: communication, resources, disposition, and bureaucratic structure. Furthermore, to analyze the implementation of the Teacher Certification Policy in the Office of the Cirebon District Education Office, this research will focus on observing these factors as observable phenomena.            Based on the results of the study showed that the implementation of the teacher certification policy in the position in the Cirebon District Education Office, in general, has gone well. In the communication factor, the subfactor of transmission and consistency of information is good, but from the subfactor of clarity, there is a problem. This lack of clarity in information includes the requirements to carry out certification. Furthermore, on the factors of resources, sub-factors of staff, information, authority is effective but the sub-factors of facilities are inadequate. Facilities in the form of facilities and infrastructure, as well as a special budget for the implementation of certification in the Cirebon District Education Office, are insufficient. The factors of the disposition of the implementor include good. The bureaucratic structure factor also supports the implementation of the policy.The Cirebon District Education Office needs to conduct an optimal socialization by empowering principals and teacher supervisors, optimizing the utilization of a database of all public and private teachers in Cirebon District. Furthermore, the Cirebon District local government prioritized funds for implementing teacher certification in positions in the Cirebon District Education Office and providing incentives for implementers as beneficiaries.